Role of adalimumab in the management of children and adolescents with juvenile idiopathic arthritis and other rheumatic conditions - Marzan KA (Dove Medical Press, 2012)
Katherine Anne B MarzanDivision of Rheumatology, Children's Hospital Los Angeles, Los Angeles, CA, USAAbstract: Treatment of children and adolescents with juvenile idiopathic arthritis and other pediatric rheumatic diseases has evolved. Where once there was only a limited arsenal of medications, with significant side effects and inadequate efficacy, today, with an increased understanding of the pathogenesis of these diseases, there is a wider variety of more targeted and effective treatments. TNF-α is a cytokine involved in a number of inflammatory pathways in pediatric rheumatic diseases. The emergence of biologic modifiers that target TNF-α has been pivotal in providing the ability to deliver early and aggressive treatment. Adalimumab, a recombinant monoclonal antibody to TNF-α, is an important therapeutic option, which affords children and adolescents with chronic illnesses an improved quality of life.Keywords: adalimumab, juvenile idiopathic arthritis, TNF-α, pediatric, rheumatic diseases, treatment